Study of inhibition of outgrowth in Bacillus cereus T by ethyl picolinate. - Pandey, N K (1977)
The effects of ethyl picolinate on germination, outgrowth, and sporulation of Bacillus cereus T were studied in a synthetic medium containing glucose. Ethyl picolinate specifically inhibited at two stages, outgrowth and sporulation. The initiation of germination and cell division was not affected. The inhibition of outgrowth by ethyl picolinate could be reversed by enrichment of inoculum with aspartic acid, asparagine, lysine, phenylalanine, and tyrosine among the amino acids and by oxalacetate. Nicotinic acid and nicotinamide also possessed this ability. Ethyl picolinate failed to block outgrowth when added to cultures incubated for a short time after inoculation. Enrichment of the medium with lysine plus zinc sulfate stimulated sporulation in the presence of ethyl picolinate to a significance degree.